The Characteristic Analysis of Caffeine Molecularly Imprinted Polymers Synthesized Using The Cooling-Heating Method, for Application as a Sensor Material - Idha Royani; Amalia Amalia; Jorena Jorena; Fitri Suryani Arsyad; Erry Koriyanti; Fiber Monado (Science and Technology Indonesia, 2021)
The cooling-heating method was used to successfully synthesize molecularly imprinted polymers on caffeine. Caffeine was used as a template and mixed with chloroform solvent, methacrylic acid as a monomer, ethylene glycol dimethacrylate as a cross-linker, and benzoyl peroxide as an initiator. The solution was stirred for 15 minutes and placed in a vial. Then it was placed in a cooler with a temperature of -5○C for 60 minutes and then inserted into an oven with an increasing temperature at 75○C, 80○C, and 85○C for 3, 2 and 1 hour, respectively. Furthermore, the repeated washing process resulted in solid polymer, which was subjected to template leaching to produce polymers with specific cavities called molecularly imprinted polymers (MIP). The resulting caffeine polymer and MIP were tested using SEM, FTIR, and XRD methods. In addition, the SEM image analysis data showed 388 cavities in the polymer after template leaching, compared to the 121 cavities in the unwashed polymer. This result was supported by the FTIR spectrum analysis which showed that caffeine MIP has a higher transmittance value than the polymer. Therefore, the caffeine concentration was significantly reduced after the leaching process. The XRD spectra showed that caffeine MIP had a smaller halfmaximum diffraction peak width (FWHM) compared to the polymer. Also, the low FWHM value depicted a larger crystalline size in the caffeine MIP compared to the polymer.